Chal̄œm phrakīat Phrabāt Somdet Phračhaoyūhūa dān kāns̄ưsān (Khana Kammakān ʻAmnūaikān Čhat Ngān Chal̨̄ong Sirirātchasombat Khrop 50 Pī, 1996)
On mass media in Thailand with reference to contribution of Bhumibol Adulyadej, King of Thailand, b. 1927.